2010
DOI: 10.1177/0883073809355821
|View full text |Cite
|
Sign up to set email alerts
|

Schizencephaly: Pre- and Postnatal Magnetic Resonance Imaging

Abstract: Schizencephaly is a rare disorder of neuronal migration that is characterized by the presence of clefts that extend from the ependymal surface of the lateral ventricles to the pial lining of the cortex. The authors present the case of a female patient with a prenatal diagnosis made by magnetic resonance imaging (MRI), her clinical course, and neurorradiological evolution following birth. A 6-year-old female, with right open lip schizencephaly, was diagnosed by means of prenatal cerebral magnetic resonance at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…24,26 Our study of 18 clefts demonstrated closure of prenatally diagnosed open clefts in 47% of cases on postnatal imaging. We qualitatively and quantitatively assessed a number of parameters to determine whether we can predict closure of prenatally open clefts.…”
Section: Discussionmentioning
confidence: 80%
“…24,26 Our study of 18 clefts demonstrated closure of prenatally diagnosed open clefts in 47% of cases on postnatal imaging. We qualitatively and quantitatively assessed a number of parameters to determine whether we can predict closure of prenatally open clefts.…”
Section: Discussionmentioning
confidence: 80%